Sigmar1’s Molecular, Cellular, and Biological Functions in Regulating Cellular Pathophysiology - Aishwarya, Richa; Abdullah, Chowdhury S.; Morshed, Mahboob; Remex, Naznin Sultana; Bhuiyan, Md. Shenuarin (Frontiers in Physiology, 2021)
The Sigma 1 receptor (Sigmar1) is a ubiquitously expressed multifunctional inter-organelle signaling chaperone protein playing a diverse role in cellular survival. Recessive mutation in Sigmar1 have been identified as a causative gene for neuronal and neuromuscular disorder. Since the discovery over 40 years ago, Sigmar1 has been shown to contribute to numerous cellular functions, including ion channel regulation, protein quality control, endoplasmic reticulum-mitochondrial communication, lipid metabolism, mitochondrial function, autophagy activation, and involved in cellular survival. Alterations in Sigmar1’s subcellular localization, expression, and signaling has been implicated in the progression of a wide range of diseases, such as neurodegenerative diseases, ischemic brain injury, cardiovascular diseases, diabetic retinopathy, cancer, and drug addiction. The goal of this review is to summarize the current knowledge of Sigmar1 biology focusing the recent discoveries on Sigmar1’s molecular, cellular, pathophysiological, and biological functions.